A small molecule drug conjugate (SMDC) of DUPA and a duocarmycin built on the solid phase. Issue 12 (27th November 2019) - Beekman, Andrew Michael; Cominetti, Marco M. D.; Cartwright, Oliver Charles; Boger, Dale L.; Searcey, Mark
Abstract : A SMDC is delivered to GCPII, an important cancer target. The payload is released by enzymes overexpressed in cancer cell lines. The SMDC relies on GCPII expression for efficacy. Abstract : In a proof-of-concept study, solid phase synthesis allowed the rapid generation of a small molecule drug conjugate in which the glutamate carboxypeptidase II (GCPII) targeting small molecule DUPA was conjugated to the alkylating subunit of the potent cytotoxin duocarmycin SA. The targeted SMDC contained a cathepsin B cleavable linker, which was shown to be active and selective against cathepsin B over-expressing and GCPII-expressing tumour cell lines.